Fritz Schneider introduces the 7th Multi-stakeholder Partnership Meeting of the Global Agenda for Sustainable Livestock - Schneider, F. (International Livestock Research Institute, 2017)
Fritz Schneider, chair, Global Agenda for Sustainable Livestock, presents context and overview of the 7th Multi-stakeholder Partnership (MSP) Meeting of the Global Agenda for Sustainable Livestock, Addis Ababa, Ethiopia.